FOSTERING INCLUSIVE PRACTICES IN PHYSICAL EDUCATION FOR DIVERSE PARTICIPATION - Axtamov Djamshed Baxromovich (Web of Journals Publishing, 2025)
This paper explores the concept of inclusion in physical education, emphasizing the importance of creating an environment where all students, regardless of their abilities, backgrounds, or needs, can actively participate. It highlights strategies for adapting activities, promoting diversity, and ensuring equal opportunities in physical education settings. The study also examines the role of educators in fostering an inclusive atmosphere that encourages teamwork, respect, and personal growth among students.
Keywords: Inclusion, physical education, diversity, equal participation, adaptive strategies, inclusive practices, student engagement, educational equity.